Incidence of oral mucositis in patients undergoing head and neck cancer treatment: systematic review and meta-Analysis - Pacheco, Raquel (2021)
This systematic review and meta-analysis aimed to assess the literature about the incidence of oral mucositis and its degrees (mild, moderate, and severe), in patients undergoing head and neck cancer treatment (radiotherapy, chemotherapy, and surgery). Addressing this issue is important since oral mucositis has a negative impact on oral health and significantly deteriorates the quality of life. Therefore, a multidisciplinary team, including dentists, should be involved in the treatment. The overall oral mucositis incidence was 89.4%. The global incidence for mild, moderate, and severe degrees were 16.8%, 34.5%, and 26.4%, respectively. The high incidence rates reported in this review point out the need for greater care in terms of the oral health of these patients.